Imaging the in vivo growth patterns of bacteria in human gut Microbiota. (1st January 2021) - Lin, Liyuan; Song, Jia; Li, Jian; Zuo, Xiaolei; Wei, Hong; Yang, Chaoyong; Wang, Wei
ABSTRACT: How to study the unculturable bacteria in the laboratory is one of the major challenges in human gut microbiota research. The resulting lack of microbiology knowledge of this "dark matter" greatly hinders further understanding of our gut microbiota. Here, to characterize the in vivo growth and division of human gut bacteria, we report the integrative use of STAMP (sequential tagging with D-amino acid–based metabolic probes) and fluorescence in situ hybridization (FISH) in a human microbiota-associated mouse model. After stable colonization of the human fecal microbiotas in germ-free mice, two fluorescent D-amino acid probes were sequentially administered by gavage, and the dually labeled peptidoglycan of the bacteria provided a chronological recording of their cell wall syntheses. Following taxonomic identification with FISH staining, the growth patterns of 32 species, including 5 currently unculturables, were identified. Surprisingly, we found that many bacterial species in the human microbiota were significantly shorter than those in the mouse gut microbiota. An imaging database for gut bacteria ̶ Microbiome Atlas was built for summarizing STAMP imaging of bacteria from different microbiotas, which can be contributed by the microbiota research community worldwide. This integrative imaging strategy and the database will promote our understanding of the bacterial cytology in gut microbiotas and facilitate communications among cellular microbiologists.